Semiconductor Corrugated Ridge Waveguide Distributed Feedback Lasers: Experimental Characterization and Design Considerations - Dridi, Kais (Université d'Ottawa / University of Ottawa, 2015)
Semiconductor corrugated ridge waveguide (CRW) distributed feedback (DFB) lasers offer compelling advantages over standard DFB lasers. Indeed, the use of surface gratings etched on the ridge waveguide sidewalls in CRW-DFB devices avoids any epitaxial overgrowth. This provides a considerable simplification in the fabrication process, reducing cost and time of manufacturing, and ultimately increasing yield. It offers also the potential for monolithic integration with other devices, paving the way towards low-cost and mass-production of photonics integrated circuits. In recent years, the re-consideration of growth-free DFB lasers has drawn considerable attention, particularly with the current state-of-the-art photolithography machines. In this work, we present an experimental investigation on two generations of InGaAsP/InP multiple-quantum-well (MQW) CRW-DFB lasers that have been fabricated using stepper lithography. An early developed 1310 nm CRW-DFB laser showed stable single mode with high side-mode suppression ratios (SMSR) (>50 dB), albeit with thresholds higher than anticipated. A subsequent single-mode 1550 nm CRW-DFB laser showed stable operation with SMSR (>50 dB) and narrow spectral linewidths (≤250 kHz), observed for a wide range of current injection. Besides, novel multi-electrode CRW-DFB lasers have been tested. The experimental investigation showed that narrower linewidth (<150 kHz) and wide wavelength tunability (>3 nm) have been recorded using different multi-electrode current injection configurations. The application of a time-domain modeling approach for semiconductor CRW-DFB lasers is then described for the first time. We numerically studied the effect of the radiation modes on CRW-DFB laser properties by using time-domain coupled wave equations. High-order corrugated gratings with λ/4 phase-shit were analyzed, where the degree of longitudinal spatial hole burning (LSHB) can be effectively reduced by means of fine tuning of the grating duty cycle. Additionally, we showed how the side-mode suppression ratio can be predicted depending on the device geometry.
Keywords: Corrigated Ridge Waveguide; Distributed Feedback Lasers